The Role of Free Radicals in Initiating and Controlling Polymerization - S.A Kholmirzayev; I.G’.Ahmedov; S.R.Khakimov; F.A.Dadakhanov (Journal of Geography, Regional Planning and Development, 2024)
This article provides a comprehensive overview of the polymerization process, highlighting its importance in the creation of diverse materials. It details different types of polymerization, their stages, and factors affecting the resulting polymer properties. The article also focuses on the role of free radicals generated from organic compounds in initiating and controlling the polymerization process. Additionally, it showcases polyethylene as a case study, exploring its production, properties, benefits, and drawbacks.